A formação continuada do professor de educação física da rede municipal da cidade de São Paulo 2008 a 2012 - Kerbej, Maria Helena Aita (2014)
Concerning the relationship between continuing education and the educational practice of physical education teacher, the question arises about his or her initial training and professional performance, and how they built over the years. Thus, since the initial training fails to give assistance to the teachers performance in their educational practices. It has formed descontextualized professionals, leading them to search for a permanent continuing education (BRACHT and CAPARROZ, 2007). According to the Ministry of Education (MEC), continuing education has the task of contributing to the training of teachers by making approach of the knowledge acquired in universities with social reality, and as a consequence, helping to improve education. Hence, the main objective of this research was to investigate how continuing education offered by São Paulo Municipal Secretary of Education (SME/SP) during the period 2008-2012, and whether she contributed to the physical education teachers educational practice, who worked in public schools, from their point of view. This investigation is a case study from the qualitative using approach the techniques of exploratory, literature review, documental analysis of the archives of SME/SP and semistructured interviews with six public network elementary school teachers I and II who took part in the continuing education offered by SME/SP. In order to complement this study and intervene in the continuing education of the teacher a focus group was conducted. This meeting aimed to promote the dialogue and the reflection about their own practice by the problematization from situations related to continuing education. Through content analysis, it was found that the objective of the training offered by the SME/SP, which was the implementation of the Curriculum Guidelines in the public network, has not been fully achieved, but when we analyze the teachers educational practice, we noticed that the experiences and dialogue which had been exchanged between them during the time of their formation, led them to reflect on their lessons and caused changes in their educational practices such as: conducting mapping, records of their on expeirnces, among others.